1980
DOI: 10.1159/000153086
|View full text |Cite
|
Sign up to set email alerts
|

Properdin Factor B Polymorphism in Afghanistan

Abstract: The distribution of properdin factor B (Bf) phenotypes and gene frequencies was studied in four populations of Afghanistan: Hazaras, Pushtoons, Tajiks and Usbeks. Significant differences between Usbeks and the other three ethnic groups were observed. The distribution of gene frequencies in Usbeks was similar to that of European populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1981
1981
1991
1991

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…A lot of studies have been performed concerning the distri bution of phenotypes and allele frequencies in various populations of the world. They are, up to now, relatively numerous for C3 [Seth and Seth, 1976] as compared to the still few for factor B [Benkmann et al, 1980]. The present report describes a study of C3 and factor B polymorphism in a pop ulation from Tunisia.…”
Section: Introductionmentioning
confidence: 74%
“…A lot of studies have been performed concerning the distri bution of phenotypes and allele frequencies in various populations of the world. They are, up to now, relatively numerous for C3 [Seth and Seth, 1976] as compared to the still few for factor B [Benkmann et al, 1980]. The present report describes a study of C3 and factor B polymorphism in a pop ulation from Tunisia.…”
Section: Introductionmentioning
confidence: 74%
“…Benkmann et al, 1980], This report shows significant variations from non-Negroid populations where allele frequencies are ranged as follows, for common types: Suhara Indians of Ecuador [Goedde et al, 1977]: Bfs = 0.978, B f = 0.011, and Saudi Arabians [Goedde et al, 1979b]: Bfs = 0.474, BfF = 0.447. About rare Bf alleles reported so far, the extreme val ues range from 0 for Mongoloid populations [Teisberg and Olaisen, 1977;Alper et al, 1972;Horai, 1976] [Benkmann et al, 1980], By comparison of Bf allele frequencies in different Negroid populations (table II), significant differences can be observed between South African Ne groes and Camerounians (%2 = 21.6, a0.05 = 3.84, 1 d.f. ), Negroes from Niger (%2 = 17.24) and US Negroes ( f = 37.4) [Mauff et al, 1976], between Camerounians and US Negroes {■/; -23.47, Negroes from Niger (x 2 = 14.41) and, finally, be tween US Negroes and Niger Negroes {■/; = 3.85) when taking into account the rare alleles.…”
Section: Resultsmentioning
confidence: 78%
“…The linkage of the Bf locus to the HLA system on human chromosome 6 is of additional interest [Allen, 1974]. Still too few studies have been reported about the distribution of various phenotypes [Benkmann et al, 1980] and alleles in the world population, and especially about Ne groid people [Alper et al, 1972;Mauff et al, 1976;Goedde et al, 1979a]. This paper presents a study of a population from Niger including a nomad people (Peul population) and a sedentary one (Djerma population).…”
Section: Introductionmentioning
confidence: 99%
“…1981]. In non-European Caucasoids the gene frequency of B f 07 = 0.076 was re ported in Usbeks [Benkmann et al, 1980], in Tunisians BJS0 7 = 0.083 [Davrinche et al, 1981], in Kabyles B f 0 7^ 0.064 [Bouali et al. 1981], and in Saudi Arabs BJS,K7 = 0.059 [Goedde et al, 1979], The gene fre quency of BJS" 7 = 0.151 found in this study is the highest reported frequency of a 'rare' Bf allotype in any population so far reported and exceeds the frequency of another rare Bf allotype, B f = 0.139 found in the Basques [Ohayon et al, 1980].…”
Section: Discussionmentioning
confidence: 98%